Thatwir Wasilah Power Point Tafau’li Li Tarqiyati Qudratu At-Thalabah ‘Ala Maharatil Kalam - Rahmah, Meutia; Sari, Latifah; Rahmatunnisak (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2023)
Purpose- This study aims to develop media interactive power point in improving speaking in Arabic lessons, determine the level of validity of media, and measure the level of effectiveness of the developed media.Design/Methodology/Approach- This study uses research and development methods based on the Dick and Carry model with special treatment from researchers. Sources of data from students, Arabic language studies teacher and expert validators were obtained throuhg observation, interviews, questionnaire and test. The data will then be analyzed qualitatively and quantitatively simultaneously with interactive analysis. The subjects of this study were is eight-sixth grade which is also called language class, with a total of 33 samples.Findings Among the results of this study were the results of the small groups with a rate of 87% and large groups with a rate of 92%, and on material validation with a rate of 100% and on media validasi with a rate of 92%. Thus media developed based on interactive power point are effective in improving thills of students in Arabic lessons.Research Limitation/Implication- the formal finding of this research is a media development to make it easier for teachers to teach, based on interactive power point can improve Arabic speaking skills for students